Ultrasensitive Freestanding and Mechanically Durable Artificial Synapse with Attojoule Power Based on Na‐Salt Doped Polymer for Biocompatible Neuromorphic Interface (Adv. Funct. Mater. 42/2021). (14th October 2021) - Hu, Luodan; Li, Lei; Chang, Kuan‐Chang; Lin, Xinnan; Huang, Pei; Zhang, Shendong
Abstract : Artificial Synapses In article number 2106015, Kuan‐Chang Chang and co‐workers, via introducing sodium acetate into polyvinyl alcohol electrolyte where mobile ions have similar roles as neurotransmitters, achieve an operation voltage as low as 1 mV and ultra‐low power consumption at an attojoule level. Combining these appealing attributes such as flexibility, freestanding ability, and biocompatibility extends the applications to a broader scale, ranging from intelligent wearable fields to environmentally benign, low power systems.